Analysis of Runway Incursion Incident Using Report for the Years 2012-2022 - Fajar Islam; Wildan Ahmad Rizkinsya Aulia (Research Synergy Foundation, 2024)
Runway incursion is a serious problem in industry flights that could threaten flight safety. This research aims to analyze the main causes of several events runway incursions that occurred in Indonesia based on KNKT reports from 2012 to 2022. The National Transportation Safety Committee is an institution of the Indonesian non-structural government that is responsible for investigating and analyzing transport accidents and incidents, including aviation, maritime, rail, and road accidents. This study covers a 10-year period to understand trends, causal factors, and safety of airport operations in Indonesia. This study employs a qualitative approach using literature study methods. The study’s findings indicate that several factors contribute to runway incursion incidents. In addition, it can be used as a basis for increasing awareness, communication, and coordination between Air Traffic Control and pilots in reducing the risk of runway incursion. Analysis showed that there was a communication error between the ATC and the pilot as the main cause. Misunderstanding of instructions, lack of coordination between Air Traffic Control with different frequencies, and lack of clear understanding are the main factors in the occurrence of runway incursions in Indonesia.